FORMULATION AND EVALUATION OF TRANSDERMAL PATCH USING ANTIOXIDANT PHYTOCONSTITUENT - Patel, Deepak Kumar; Gidwani, Bina; Gupta, Anshita; Sahu, Jyoti; Kaur, Dr. Chanchal Deep (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Conventional drug delivery system has many problems so bulk of research has now shiftedfrom synthetic drugs to herbal drugs. This is possible because of the vast variety of bioactivemolecules in the plants and their higher safety margin. This present study is focused on theuse of curcumin, the active constituent of Curcuma longa (haldi), and belonging to familyZingiberaceae as an antioxidant agent. The main objective of present work was to develop thetransdermal patch of curcumin using polymer blends so that minimize the side effects andmaximize the therapeutic efficacy. The formulations were also evaluated for weight variation,moisture uptake, thickness, moisture content, and folding endurance. Shows satisfactoryresults.